Pemanfaatan Aplikasi Plotagon Sebagai Media Pembelajaran Bahasa Arab Kelas X MAN - Adam Mudinillah; Amrina; Siti Mahmudah Indarpansa (Jurnal Pendidikan Bahasa Arab dan Budaya Islam, 2022)
The use of learning media to teach Arabic language subjects in the 21st century era must continue to grow and develop because of the challenges and needs of life as technological advances continue to increase and even feel very threatening. Therefore, there is a need for the development of Arabic language learning media so that it does not lag far behind with technological advances so that learning Arabic no longer feels boring for students. Such as by applying the Plotagon application-based learning media that is very suitable for the type of life of millennial children who have a hobby by looking at photos, videos and even movies. The method used in this research is a descrciptive qualitative method by collecting student data based on research results, which the purpose of this research is to introduce and to facilitate learners in the learning process and useful to know the meaning of the material presented, so that students can benefit such applications on learning Arabic.